Cloning and expression of Fasciola hepatica enolase gene and efficacy of recombinant protein in the serodiagnosis of sheep fasciolosis - Celik, Figen; Simsek, Sami; Selcuk, Muhammed Ahmed; Kesik, Harun Kaya; Kilinc, Seyma Gunyakti; Celik, Burcak Aslan (Elsevier, 2023)
Fasciolosis caused by Fasciola hepatica is a disease of zoonotic importance that is common worldwide and can cause serious problems in farm animals, some wild animals and humans. The development of diagnostic kits for the correct diagnosis of fasciolosis in sheep is important in terms of preventing yield losses. With this study, it is aimed to clone and express the enolase gene to be isolated from adult F. hepatica and to determine the effectiveness of the recombinant antigen in the serodiagnosis of sheep fasciolosis. For this aim, primers were designed to amplify the enolase gene from the F. hepatica enolase sequence, mRNA was isolated from F. hepatica adult fluke obtained from an infected sheep followed by cDNA was obtained. Enolase gene was amplified by PCR and the product was cloned and then expressed. The efficiency of the purified recombinant protein was displayed by Western blot (WB) and ELISA using positive and negative sheep sera. As a result, the sensitivity and specificity rates of the recombinant FhENO antigen were 85% and %82.8 by WB while the rates were 90% and 97.14% by ELISA, respectively. At the same time, in sheep blood sera samples collected from the Elazig and Siirt provinces of Turkey, 100 (50%) of 200 sera were found to be positive by WB and 46 (23%) were found to be positive by ELISA. The most important problem in ELISA was the high cross-reaction rate of the recombinant antigen used, as in WB. In order to prevent the cross-reactions, it will be useful to compare the genes encoding the enolase protein of parasites from the closely related parasite family, and select the regions where there are no common epitopes, and clone them and test the purified protein.
Keywords: Fasciola hepatica; Sheep; Enolase; Cloning; Western Blot; ELISA